Empedobacter brevis Meningitis in a Neonate: A Very Rare Case of Neonatal Meningitis and Literature Review - Deepak Sharma; Ankur Patel; Priyanka Soni; Pradeep Sharma; Basudev Gupta (Case Reports in Pediatrics)
Empedobacter brevis is gram-negative bacilli that belongs to Flavobacteriaceae family. It was previously known with name of Flavobacterium breve. The reservoir of these bacteria is soil, plants, water, food, hospital water sources, including incubators, sinks, faucets, tap water, hemodialysis systems, saline solutions, and other pharmaceutical solutions. We report a case of term female newborn, admitted with complaint of respiratory distress developing soon after birth and developed clinical features of sepsis at age of 92 hours of postnatal life. The sepsis screen was positive and blood culture and cerebrospinal fluid showed growth of Empedobacter brevis that was resistant to multiple antibiotics. The neonate was treated with appropriate antibiotics and was discharged successfully. The novelty of the case report is that this is the first case report of neonatal sepsis caused by Empedobacter brevis.